Associação entre fatores de riscos sistêmicos e a densidade óssea em radiografia panorâmica: um estudo descritivo retrospectivo - Yokota, Matheus Gabardo (2021)
The osseointegration of dental implants strictly depends on an adequate primary stability at the insertion site and the low bone density can lead to micro movements of these implants, making their success difficult and possibly even failing. The goal of this work was to carry out a retrospective descriptive study on digital panoramic radiographs taken at the State University of Western Paraná – UNIOESTE to assess the relationship between systemic risk factors of patients and mandibular bone density. Also adapt the software BmA-DDX - Bone Microarchitecture by Digital Dentistry X-RAY - System for the Evaluation of Bone Microarchitecture of digital dental radiography for possible association with bone densitometric diagnosis. Panoramic radiographic images were obtained from the Radiology Laboratory at Unioeste, between 2017 and 2021. Two hundred and sixty-three medical records of patients who had digital panoramic radiographs and complete medical records were used in this study. In each radiograph, samples were collected using a standardized marker of 30x50 pixels, in the reference areas, in order to obtain the count of trabecular pixels. The averages of trabecular pixels were significantly higher for normal radiographs compared to suspicious radiographs, considered to have lower bone density (p<0.05). There was a higher frequency of female patients with suspicious radiographs, hypertension, osteoporosis, asthma, rheumatism, back pain, arthritis and total edentulousness. Although the software is not recommended for the diagnosis of osteoporosis, the method allowed the assessment of bone density in samples collected in normal and suspected cases, therefore, it can serve as a low cost alternative to assist dental surgeons in the diagnosis and referral of patients with bone changes, especially when there is an association with other risk factors.